REFLEKSI FILOSOFIS MENGADA DALAM KEBERMAKNAAN HIDUP MANUSIA MENURUT TERANG METAFISIKA MARTIN HEIDEGGER - Wendi Setiawan (Aggiornamento, 2024)
Man lives in the world with all his being. He is present, there must be a point. hence the need for that to be the focus in this article. This focal point is based on Martin Heidegger's metaphysical thinking on Being and Time. So, to answer this, the method used in this research is qualitative research based on literature studies. Thus, the author is able to provide findings and conclusions as to how the meaning of life is present in the way humans exist and how Heidegger views it with his metaphysics. So, the finding present in this article is how metaphysics sees the existence of humans in Heidegger's metaphysics. Furthermore, how the meaning of life can be created through the existence of humans. Not to forget also that the main finding is the personal way of seeing it as a novelty in this article. The result obtained is that humans are able. Keywords: Heidegger's metaphysics, Being and Time, existing, the meaning of life